Al Qaeda’s Resurgence in Syria : A New Caliphate? - Soliev, Nodirbek (2019)
Even as the so-called Islamic State (IS) embarks on a new phase of global expansion, as evidenced by the recent Easter attacks in Sri Lanka, its jihadist rival Al Qaeda is enjoying a resurgence in the Syrian conflict theatre.